Providing Several Skills to Treat Complex Infectious Stones of Solitary Kidney in a Patient Failed to Undergo Percutaneous Nephrolithotomy: A Case Report - Feng, Dechao; Wei, Wuran (Frontiers in Surgery, 2021)
Conservative treatment is closely associated with renal deterioration for patients with renal staghorn stones. It is well-recognized that percutaneous nephrolithotomy (PCNL) is recommended as the first-line treatment of renal stones larger than 2 cm due to its higher stone clearance and cost-effectiveness when compared with other treatment alternatives, such as shockwave lithotripsy and flexible ureteroscopy (FURS). Besides, our findings indicated that miniaturized PCNL could be served as an alternative to PCNL with a higher stone-free rate and a lower hemorrhage risk. Despite the higher cost-effectiveness of PCNL, the management of staghorn stones are still controversial in some special situations, such as a solitary kidney. Herein, we present a case with complex infectious stones of a right-sided solitary kidney, complaining of persistent pain in the right waist. The rarity of this case is that it is difficult to encounter these cotton-like staghorn stones which are clinically resistant to holmium laser lithotripsy, and the particularity is that the patient with solitary kidney failed to undergo PCNL. We found that the combination of intermittently high-frequency oscillation and flexible ureteroscopy forceps might contribute to treat the complex infectious stones in a patient with solitary kidney. Our surgical experience might be beneficial to such patients undergoing flexible ureteroscopy in clinical practice.